Diplomasi Paralel dalam Hubungan Internasional Kontemporer: Studi Kota Bandung dalam Jejaring UNESCO Creative Cities Network - Muthi Najwa Hanifa; Windy Dermawan (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2026)
This research analyzes the governance and practices of Bandung City’s parallel diplomacy in developing its identity as a City of Design. Using the concept of parallel diplomacy, the study examines the roles of governmental and societal actors in international collaboration supported by UNESCO. A qualitative approach was employed through in-depth interviews with the Department of Culture and Tourism of Bandung City and the Bandung Creative City Forum (BCCF), supported by document analysis and secondary literature. Overall, Bandung’s parallel diplomacy functions through synergy between governmental and societal actors, complementing Indonesia’s national diplomacy agenda in strengthening the creative economy and culture